Adsorption separation of heavier isotope gases in subnanometer carbon pores - Ujjain, S.K.; Bagusetty, A.; Matsuda, Y.; Tanaka, H.; Ahuja, P.; Tomas, Carla de; Sakai, M.; Vallejos-Burgos, F.; Futamura, R.; Suarez-Martinez, Irene; Matsukata, M.; Kodama, A.; et al. (NATURE RESEARCH, 2021)
Isotopes of heavier gases including carbon (13C/14C), nitrogen (13N), and oxygen (18O) are highly important because they can be substituted for naturally occurring atoms without significantly perturbing the biochemical properties of the radiolabelled parent molecules. These labelled molecules are employed in clinical radiopharmaceuticals, in studies of brain disease and as imaging probes for advanced medical imaging techniques such as positron-emission tomography (PET). Established distillation-based isotope gas separation methods have a separation factor (S) below 1.05 and incur very high operating costs due to high energy consumption and long processing times, highlighting the need for new separation technologies. Here, we show a rapid and highly selective adsorption-based separation of 18O2 from 16O2 with S above 60 using nanoporous adsorbents operating near the boiling point of methane (112 K), which is accessible through cryogenic liquefied-natural-gas technology. A collective-nuclear-quantum effect difference between the ordered 18O2 and 16O2 molecular assemblies confined in subnanometer pores can explain the observed equilibrium separation and is applicable to other isotopic gases.